Femorofemoral Bypass using Accessory Saphenous Vein Graft in Superficial Femoral Artery Total Occlusion: A Case Report - Aditya, Putu Garry Cori; Nababan, Victor Jesron; Satria, Darma (Universitas Airlangga, 2024)
Highlights: 1. While GSV has its advantage as a conduit of choice, in certain cases it might not be a suitable option for the patient depending on how complex the case is. 2. This article discusses the usage of ASV as alternative vein conduit and it shows an interesting result. - Background: PAD can be treated with either endovascular intervention and open surgery. Great saphenous vein (GSV) is the most commonly used vein conduit for infrainguinal vascular bypass. Case Summary: 38-years old man presented with intermittent claudication for 2 months and diabetic foot ulcer on his left cruris. Left pedal artery pulse was absent with ABI of <0.4. Angiography showed a chronic total occlusion of left superficial femoral artery (SFA). Upon intraoperative, an aneurysmatic GSV and a good accessory saphenous vein (ASV) were found through the same incision. Thus, ASV was chosen as the vein conduit. Postoperative period of 3 days was steady. Two months follow up revealed his ability to walk normally, good pulse and perfusion, and no deterioration on his ulcer. Discussion: GSV performed better than prosthetic conduits with a 5-year patency rate of 80%, thus it becomes the conduit of choice in 2024 ESVS guideline. However, the GSV was found inadequate, and the prosthetic graft was unavailable, in this case. ASV was decided to be more suitable to be used as an alternative vein conduit. In the absence of adequate GSV, alternative autologous vein can be used and even perform better than prosthetic conduits.